Overall Quality of Life Assessment in the Patients Undergoing External Beam Radiation in Outpatient Radiation Oncology Department - Rashmi Koul (International Journal of Hematology-Oncology and Stem Cell Research, 2015)
Background: The impact of treatment on cancer patients’ quality of life (QoL) has been the focus of a variety of longitudinal studies in English literature for past decade. The measurement of patient-reported outcomes which includes health-related quality of life is a new important initiative which has emerged and grown over the past three decades. Following the development of reliable and valid self-reported questionnaires, health-related quality of life has been assessed in tens of thousands of patients and a wide variety of cancers. With growing information, feedback and experience, the quality of the health-related QOL studies has improved a lot. We expect in near future more methodologically robust studies will be done in a scientific way to answer unanswered questions. Methods: As part of a Dean's summer project, a survey was undertaken to facilitate a more complete description of the quality of life experience in patients with histological diagnosis of cancer undergoing external beam radiation as an outpatient at Allan Blair Cancer Center, Regina, Canada. The questionnaires had two major components: depression and global QOL. The depression was measured by the Zung Self-Rating Depression Scale which is a short self-administered survey to quantify the depression status of a patient. Results: Overall, only the equation associated with the outcome of QoL - Physical well-being was significant. That data indicated that only the variable of age was a significant predictor. A positive relationship was present indicating higher levels of depression when patients received chemotherapy or narcotics. Breast cancer patients were less depressed than lung cancer patients. Conclusion: Cancer and its related treatment is an important health issue influencing QoL. The study has revealed that the use of chemotherapy and narcotics has a significant impact on the quality of life (QoL).